PERTUMBUHAN Nephentes mirabilis PADA MEDIA DENGAN PENAMBAHAN ARANG AKTIF DAN PENGGUNAAN SUMBER EKSPLAN BERBEDA - Susiyanti . (Jurnal Agroekoteknologi, 2010)
ABSTRACT Indonesia has a rich biological diversity due to its varied climatic, altitudinal variations and ecological habitats. There are two methods of conservation: in situ and ex situ onservation, both are complementary to each other. In situ methods allow conservation to occur with ongoing naturalevolutionary processes, ex situ conservation via in vitro propagation also acts as a viable alternative for increase and conservation of populations of existing bioresources in the wild and to meet the commercial requirements.  The research was aimed to determine the source of explants and consentration of activated carcoal. This research has been conducted in 4 months has been carried out during March to July 2008 in the Laboratory of Indonesia Centre for Biodiversity and Biotechnology, Nagrak Cilubang-Bogor. This research using completely randomized design arranged as a factorial with two factors, and 5 replicates. The first factor is sources of explants with two levels different (up and down of shoot). The second factor is the consentration of activated carcoal with 5 levels, namely: 0,1,2,3 g.l-1.  The results showed that up of shoot show the best growth performance; while the best medium to increase explant regeneration with 2 g.l-1 activated carcoal.Keywords: in vitro propagation, Nephentes mirabilis, activated charcoal, source of explants.